The Pedagogical Knowledge of Mathematics Teachers on How to Teach Geometry Module for Sixth Grade Students: A Case Study - Ibtisam Hamad; Refa Ramahi (دراسات: العلوم التربوية, 2021)
The study aims to investigate the pedagogical teachings of mathematics teachers as taught in a sixth-grade geometry unit. To achieve the goal, a descriptive qualitative approach was implemented. This approach utilized two tools: a questionnaire and an oral interview. The first tool is represented by questionnaire about pedagogical content knowledge (PCK) of geometry for the sixth grade. All 27 of the study participants, who are mathematics teachers currently enrolled in the Master of Education/ Mathematics Education Concentration Program at Birzeit University, completed the questionnaire. The results were collected and analyzed. The teacher who received the highest score on the questionnaire was selected for an oral interview (Abeer). The oral interview questioned Abeer’s knowledge of who to teach the content of geometry for the sixth grade. The results concluded that Abeer's knowledge of how to teach geometry content for sixth grade was good, except for her limited knowledge of learning resources.